Metal-insulator-superconductor transition in nickelate-based heterostructures driven by topotactic reduction - Han, Kun (2024)
The discovery of superconductivity in doped infinite-layer nickelates has attracted great interest recently. Here, a metal-insulator-superconductor transition is demonstrated by engineering the process of topotactic reduction. By employing topotactic reduction, a superconducting Nd0.8Sr0.2NiO2 layer is obtained from high-quality Nd0.8Sr0.2NiO3, which is characterized by layer-by-layer growth and low room-temperature resistivity, rather than the low-quality Nd0.8Sr0.2NiO3 with mixed phases. Moreover, an insulating intermediate state is uncovered within the transition from metallic Nd0.8Sr0.2NiO3 to superconducting Nd0.8Sr0.2NiO2, corresponding to a non-monotonic modulation of resistivity driven by topotactic reduction. In the incompletely reduced Nd0.8Sr0.2NiO2+δ, residual oxygen atoms in the Nd/Sr plane disrupt the long-range order of the infinite-layer structure, resulting in suppressed superconductivity with a low transition temperature and non-zero residual resistivity. On the other hand, the superconductivity is optimized in the fully reduced sample, where a sign change in the Hall coefficient is always observed at low temperatures. Our study highlights the diverse electronic states achievable by controlling topotactic reduction, providing valuable insight into the understanding and manipulating of superconductivity in infinite-layer nickelates.